Yamabiko gakkō - Muchaku, Seikyō 1927- (Daiei, 1997)
Dramatization of the life of Muchaku Seikyō and his experiences teaching in rural Yamagata prefecture that led to his compilation of the bestselling collection of children's writings, Yamabiko gakkō
Original: Japan 1952. - Bildformat 1.37:1
Keywords: Muchaku, Seikyō / 1927- / Drama; Muchaku, Seikyō / 1927-; Feature films; Elementary school teachers / Japan / Drama; Elementary school teachers; Japan; Film